PENGARUH PERAN KONSULTAN PAJAK TERHADAP PENERAPAN SELFT ASSESMENT SYSTEM TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus Pada Wajib Pajak Badan Pada KPP Pratama Ilir Timur Palembang) - Basuki, Rahmad (Balance : Jurnal Akuntansi dan Bisnis, 2018)
The purpose of research on the role of tax consultants in the self assessment system on taxcompliance (case studies on corporate taxpayers in KPP East Ilir Palembang ) is todetermine the effect of a tax consultant role to the knowledge of the taxpayer, the taxpayer'sperception of justice and tax compliance. This study also aimed to determine the effect ofknowledge and perceptions of fairness taxpayer taxpayers on tax compliance. This studywas conducted using quantitative research and analysis using simple and multiple linearregression, in which the role of tax consultants are independent variables, while theknowledge of the taxpayer, the taxpayer perceptions of fairness and tax compliance as thedependent variable.This study uses the entire population of companies that use the services of a tax consultantin South Sumatra, while the data collection is done by the method of literature review,questionnaire by the respondents as well as documentation for further studies discussionand analysis. The results showed that the variable role of tax consultants have a significantinfluence on the knowledge of the taxpayer, taxpayer fairness perceptions, and taxpayercompliance registered in KPP East Ilir Palembang.The results also showed that by the variable knowledge taxpayer has a significant influenceon tax compliance is registered in KPP East Ilir Palembang.Variabel taxpayer fairnessperceptions have a significant influence on tax compliance is registered in KPP East IlirPalembang.Variabel role of tax consultants, knowledge taxpayer, and the taxpayer'sperception of fairness simultaneously (together) have a significant effect on tax compliance isregistered in KPP East Ilir Palembang.